Estimating the global burden of scabies: what else do we need?. (1st February 2021) - Cox, V.; Fuller, L.C.; Engelman, D.; Steer, A.; Hay, R.J.
Summary: Scabies is one of the most common disorders identified in any estimate of global skin disease prevalence. Furthermore, quantifying its impact on individuals and societies has been problematic. There has been a lack of clear case definitions and laboratory tests. There have been few epidemiological studies, particularly those focusing on low‐income countries, variation in prevalence within high‐income countries, or estimates of the effect of scabies on health beyond the skin, such as renal disease or mental wellbeing. Economic studies are also lacking. However, the new strategy of integrating surveillance for skin Neglected Tropical Diseases may well produce advancements on these issues, in addition to providing an overarching structure for health improvement and disease control.